Doing theology in the era of HIV/AIDS: A critical evaluation of the Theology and Religious Studies Department, University of Botswana - Ruele, Moji (Missionalia: Southern African Journal of Mission Studies, 2001)
This article descriptionbes and evaluates the role, of the Department of Theology and Religious Studies at the University of Botswana in the fight against HIV/AIDS. Several members of staff and students have undertaken research projects and papers have been read at departmental seminars on HIV/AIDS. Members of the department have been involved in community service to victims of AIDS, including counselling and burying the victims.
Free